(Perception of Farmer’s Community Toward Local Wisdom on Corn Crops Business Activities at Sonraen Village, South Amarasi Sub-District, Kupang Regency - Patrisno I. Selan; Selfius P. N. Nainiti; Alfetri N. P. Lango (Undana Press, 2022)
Research on farmers' perceptions of local wisdom on corn farming activities has been carried out at Sonraen Village, South Amarasi District, Kupang Regency on August to September 2019 with the aim of: (1) to find out what Local Wisdom still survives on corn farming activities in the research area; (2) To find out what values ​​are contained in Local Wisdom on corn farming activities. (3) to analyze the extent of the perception of the farming community on local wisdom on corn farming activities. The method used in this research is in-depth interview method. Determining the location of research carried out deliberately. The analysis shows that; (1) Local wisdom that still survives are tradition of. Tof Rene tradition Tsifo Nopo tradition Tsimo Tsuan tradition Toit Uran tradition Eka Hoe tradition Tkau Uran tradition Tatam Pena Tauf and tradition Tanon tradition Seki Pena tradition Tnau Baraif and tradition Save So’e; (2) The Most Prominent Values Found in Each Tradition Include : Spiritual Values, Pandeistic Values, Togetherness Values and Religious Values. (3) the level of perception of the farming community towards local wisdom on corn farming activities at the village of Sonraen. South Amarasi Sub-District. Kupang Regency is on the Good category, with the presentation achieving the score at 77.33%.